Statistical Yearbook for Latin America and the Caribbean 2017 - Nations Unies (United Nations, 2018)
The 2017 edition of Statistical Yearbook for Latin America and the Caribbean presents a set of basic statistics that characterize the economic, sociodemographic and environmental situation of the region in relation to a particular period. This information is part of the set of statistics available at CEPALSTAT, the database portal and statistical publications of ECLAC.